2019
DOI: 10.1186/s42155-019-0059-z
|View full text |Cite
|
Sign up to set email alerts
|

Precipitating hydrophobic injectable liquid (PHIL) embolic for the treatment of a uterine arteriovenous malformation: a technical report

Abstract: Objective: Uterine arteriovenous malformations (AVM) are unusual causes of vaginal bleeding. Although hysterectomy is the definitive treatment; uterine artery embolization (UAE) provides an alternative therapeutic option. This case presents a technical report of a uterine AVM treated successfully with transcatheter UAE using precipitating hydrophobic injectable liquid (PHIL) embolic agent. Case report: A 41-year-old female, gravida 6, para 4, miscarriage 2, including a molar pregnancy 15 years prior, presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Table 1 summarizes the liquid embolics that are discussed in this review. Shear-Thinning Biomaterials [88,89] Silk Elastin Protein (SELP) [90][91][92] Poly(Ethylene Glycol) Hydrogel Embolization System (HES) Instylla Embrace [92][93][94][95][96] Eudragit [97][98][99][100] Calcium Alginate [101][102][103][104][105][106] Ethylene vinyl alcohol copolymers Squid and Squid Peri [107][108][109][110][111][112][113][114][115][116][117] Onyx Poly(lactide-co-glycolide) and poly(hydroxyethyl methacrylate) PHIL [159][160][161][162][163][164][165][166][167] Iodinated polyvinyl alcohol EASYX [168][169][170][171] 3.1. Polymerizing Liquid Embolics…”
Section: Liquid Embolicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes the liquid embolics that are discussed in this review. Shear-Thinning Biomaterials [88,89] Silk Elastin Protein (SELP) [90][91][92] Poly(Ethylene Glycol) Hydrogel Embolization System (HES) Instylla Embrace [92][93][94][95][96] Eudragit [97][98][99][100] Calcium Alginate [101][102][103][104][105][106] Ethylene vinyl alcohol copolymers Squid and Squid Peri [107][108][109][110][111][112][113][114][115][116][117] Onyx Poly(lactide-co-glycolide) and poly(hydroxyethyl methacrylate) PHIL [159][160][161][162][163][164][165][166][167] Iodinated polyvinyl alcohol EASYX [168][169][170][171] 3.1. Polymerizing Liquid Embolics…”
Section: Liquid Embolicsmentioning
confidence: 99%
“…The authors have suggested further studies for evaluating safety and efficacy of PHIL. In a technical report in 2019, Kurda et al demonstrated the treatment of uterine AVM by transcatheter uterine artery embolization using PHIL [165]. The authors have mentioned that the process was safe, effective and successful proving an alternative method for hysterectomy.…”
Section: Phil Tmmentioning
confidence: 99%